2019
DOI: 10.1088/1742-6596/1397/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subsurface Lithology in Sendang Mulyo, Purwoharjo Village, Samigaluh Subdistrict, Kulon Progo Regency

Abstract: Research aimed to determining the lithological conditions subsurface of landslide areas in Sendang Mulyo, Purwoharjo Village, Samigaluh Subdistrict, Kulon Progo Regency by geoelectric and microseismic methods. The research had been conducted after knowing the subsurface lithology conditions, it could anticipate landslides as disaster mitigation. The location of research is on a hillside in Purwoharjo Village. The research located on that area because the history landslides. The area is the longest landslide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Parameters in the form of P wave velocity (Vp), S wave velocity (Vs), and density are used as limits to obtain a model that approximates the actual subsurface structure. The parameters in this study refer to previous studies [8,[17][18][19]. Based on previous research, researchers made parameters in the research area which can be seen in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameters in the form of P wave velocity (Vp), S wave velocity (Vs), and density are used as limits to obtain a model that approximates the actual subsurface structure. The parameters in this study refer to previous studies [8,[17][18][19]. Based on previous research, researchers made parameters in the research area which can be seen in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by [6][7] shows the dominant frequency and amplification values in Samigaluh District. While research [8] shows the value of shear wave velocity and lithology located in Samigaluh District.…”
Section: Samigaluhmentioning
confidence: 94%
See 1 more Smart Citation
“…Other geological types mainly consist of alluvium, colluvium, and local igneous rocks. In situ studies using geophysical methods revealed the existence of sliding planes in several sites within the Catchment (Katriani et al 2019;Pratiwi et al 2019;Widyadarsana and Hartantyo 2021;Dzakiya et al 2023).…”
Section: Introductionmentioning
confidence: 99%